Discharging Mrs. Fox: A Team-Based Interprofessional Collaborative Standardized Patient Encounter - Anna Richmond (Association of American Medical Colleges, 2017)
Introduction In 2003, the Institute of Medicine recommended that interprofessional education be incorporated into the training programs of health care professionals. However, many logistical challenges hinder formal interprofessional learning in health care profession programs. Methods This resource is a 3-hour interprofessional small-group session designed for health professions student teams to engage in a standardized patient encounter, each team member contributing a profession-specific perspective to create a collaborative care plan across five discharge decisions. The activity includes a simulated standardized patient encounter and debrief session wherein students discuss the role of bias and communication and create a collaborative care plan. Results Following the activity, participants were surveyed about the value of the educational experience. Over 12 months, 106 students (81 medicine, nine nursing, 16 pharmacy) participated in the interprofessional activity. Eighty-four students responded to the postevent survey (79% response rate). Students were confident that the experience helped them integrate profession-specific knowledge, create a shared care plan, and understand how interprofessional collaboration contributes to quality care. The debriefing session and interprofessional interaction were an integral component of the experience. Discussion This resource is a feasible interprofessional small-group activity that has been implemented without excessive faculty time or institutional resources. It is adaptable to institutional needs, local resources, level of trainee, and professions. The session provides interprofessional students the opportunity to engage with one another and with the patient in a collaborative decision-making activity focused around a critical transition of care.